George Eliot, her work in literature - Fryhofer, Florence Eleanor (My University, 1895)
Introduction: Far away in England, in one of these rural districts where the quiet roads are bordered with hedgerows, and stately elms cast their shadows; where busy were, well kept farms, the red brick school-house, and the broad pastures speak of thrift and prosperity; and all suggests sweet repose alike to werid and eye, Mary Anne Evans was born Nov. 22, 1819. She was destined to become the great English author, known to the world as George Eliot
Citation: Fryhofer, Florence Eleanor. George Eliot, her work in literature. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: England; Prosperity; Mary Anne Evans; George Elliot; Theses; Manuscripts (documents)